Environmental Law Enforcement In Law Number 32 of 2009 Concerning Environmental Protection and Management - Valencia Prasetyo Ningrum (Asian Journal of Social and Humanities, 2023)
Everyone is part of society who has the same rights, obligations and roles in environmental management. The foundation of the constitution has also provided guarantees listed in Article 28H paragraph (1) of the Constitution of the Republic of Indonesia. The involvement and role of the community was then reaffirmed in Law no. 32 of 2009 concerning the Protection and Management of the Environment, in Article 70. There are several aspects of law enforcement carried out in the environmental field. Law enforcement in the environmental field can be classified into 3 (three) categories, namely Administrative or State Administration environmental law enforcement, Civil environmental law enforcement and Criminal environmental law enforcement. Even though the Government has issued regulations regarding environmental law enforcement that have been planned in a directed manner, there are still many obstacles and obstacles encountered in implementation in the field. Obstacles and obstacles in enforcing environmental law in Indonesia are due to the government's lack of attention to problems that arise in society regarding enforcing environmental law related to the lack of outreach to the public regarding environmental law, not to mention the lack of awareness from the public of the importance of environmental management, as well as a legal culture that is still poor in budget management for the environmental sector.